The Effect of Brand Experience, Brand Loyalty, and Self-Congruity on Positive Word of Mouth with Brand Love as an Intervening Variable: A Study in Banjarbaru Starbucks Customers - Prihatiningrum, RR. Yulianti; Sutan Naufal Al Khadafi (Open Access Indonesia Journal of Social Sciences, 2024)
Several factors that can influence positive WOM are brand experience, brand loyalty, self-congruity, and brand love. Brand experience, created by Starbucks in Banjarbaru, can be a positive or negative experience experienced by customers when interacting with the brand. A positive brand experience can make customers feel comfortable and happy to be in the cafe and satisfied with the quality of the products and services they receive. High self-congruity can make customers feel comfortable and happy interacting with a brand and make consumers more loyal to that brand. This research method uses a questionnaire with 165 Starbucks Banjarbaru customers as a sample and was selected from the entire customer population. Variable measurement uses the Likert Scale technique with a weight scale from 1 to 5. Data analysis uses partial least squares with the help of the SmartPLS program. The research results show that brand experience, brand loyalty, and self-congruity have a positive effect on positive word of mouth. Brand love mediates the influence of brand experience, brand loyalty, self-congruity on positive word of mouth.